Rendre la conservation de l’agrobiodiversité mexicaine gouvernable ou le difficile transcodage des savoirs scientifiques - Jean Foyer; Marianna Fenzi (Revue d'ethnoécologie)
This article offers an analysis of the flagship program for the conservation of the diversity of Mexican maize - the Programa de Conservación de Maíz Criollo (PROMAC) - from its design at the level of national institutions to its implementation at the local level, including the regional administrative level. We show whether or not the different types of knowledge mobilized contribute to the various operations meant to make the issue of maize landraces conservation readable and governable. We also highlight how other types of factors (path dependence, institutional and administrative habits, lack of resources) turn out to be determining forces in the realization of the program.